Compensation for non-pecuniary damage in labor law is an important guarantee of the protection of workers’ rights - Rossolov, V. V. (Науковий вісник Ужгородського національного університету. Серія Право, 2024)
The article is devoted to the study of the institution of compensation for moral damage in the field of labor, i.e. in cases where the employee’s labor rights are violated by the employer, and as a result, moral damage is caused, which is subject to compensation. Since the issue of compensation for moral damage in labor law remains debatable to this day, as there is no unambiguous scientific or legislative solution to it. Although the institution of compensation for moral damage in the field of labor is an important guarantee of the protection of workers’ rights. During the research, the current domestic legislation and the views of scientists on the raised issue were analyzed. In particular, it is stated that compensation for non-pecuniary damage in labor law has its own characteristics compared to compensation for non- pecuniary damage in civil law. Thus, the specifics of compensation for non-pecuniary damage in the field of labor lies in the subject structure of this legal relationship - the employee and the employer, where the employer has the obligation to compensate non-pecuniary damage, and the employee has the right to receive it in the presence of negative consequences of the violation of labor rights. Attention has been drawn to the fact that compensation for moral damage in labor law is proposed to be considered in three aspects: as compensation for moral damage caused to the employee; as an independent, special and universal type of employer’s responsibility; and as a way of protecting the rights of the employee in labor relations. It was concluded that the labor legislation regarding the legal regulation of issues of compensation for moral damage to the employee needs improvement, since it lacks a definition not only of compensation of moral damage in labor law, but also of moral damage in labor law, which , in turn, leads to the fact that the inflicted moral damage is not actually perceived as damage, it is simply ignored. At the same time, although the introduction of the institution of compensation for moral damages in labor law did not solve all the problems regarding the protection of human labor rights, it is evidenced by the fact that the constitutional provisions on the recognition of a person as the highest social value and the guarantee of his physical and moral safety by every state are gradually being implemented in the labor legislation.